As perspectivas da ampliação da cidadania da criança e do adolescente e a adoção por pessoas em uniões homoafetivas - Baranoski, Maria Cristina Rauch (2009)
This search has the purpose to analyze the possibility of children´s and adolescents´ adoption for people in homo affective union, as one of the alternatives for the extension of citizenship and of the right that children and adolescents have to a family and a community life. The search has a quantitative and qualitative character, being held through the following methodology: systematization of theoretical and methodological basis of the major analytical categories: citizenship, child and adolescent, family, adoption, homo affective unions. Through this search it´s possible to visualize the debate on the homosexual adoption in contemporary Brazil, identifying prospects and characterization of the Institute of adoption as a mean of integral protection for children and adolescents that are on shelters. On this systematization, it was of fundamental importance the analysis on the children´s and adolescents´ rights to have a life in a family and community environment, and the dynamic of human relationships that result in a rethink on the types of family that already exist. In the process, it was performed a fieldwork research with the significant subjects who experience the reality studied (professionals and militants), through their testimonials about the prospects to expand the citizenship of children and adolescents and the adoption by people in homo affective unions. The synthesis of this process resulted in the identification of a positive outlook for the researched topic, even though it was structurally and culturally determined, opening up possibilities and challenges to children´s citizenship, adolescents and to people in homo affective unions wishing to adopt them.